Visualizing Art Education in Secondary Schools through AR/VR Technologies - Usmonov Umid Farxodovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: The integration of Augmented Reality (AR) and Virtual Reality (VR) technologies into secondary school art education presents a transformative approach to teaching and learning. By providing immersive and interactive visual experiences, AR and VR enable students to better understand complex artistic concepts, historical contexts, and creative techniques. This study explores the pedagogical benefits of AR/VR applications in art lessons, highlighting their potential to enhance students’ engagement, creativity, and critical thinking. Furthermore, the paper examines practical implementation strategies and discusses challenges related to accessibility, teacher training, and curriculum adaptation.